Optimal Tide Gauge Location for Tsunami Validation in The Lembeh Island, North Sulawesi - Sesar Prabu Dwi Sriyanto; Ping Astony Angmalisang; Lusia Manu (Geological Agency, 2022)
DOI:10.17014/ijog.9.3.315-327The tsunami early warning system in Bitung does not work optimally, because there is no buoy as a marine equipment for tsunami validation before reaching the coastal area. The lack of buoy can be replaced by placing a tide gauge on the east coast of Lembeh Island. To determine the optimal tide gauge location, the simple additive weighting (SAW) method was used with three criteria. Those three criteria are the potential of tsunami detection, sufficient evacuation time, and an appropriate site for tide gauge installation. Numerical tsunami modeling is used to calculate the first two criteria. The third criterion is a limiting factor, because the tide gauge can only be installed on the dock. Therefore, there were only five candidate locations on the east coast of Lembeh, namely Dorbolang, Pancuran, Posokan, Motto, and Lirang. The result, Posokan is the best location for tide gauge placement with a total score of 2.884. Based on the simulation, an additional tide gauge in Posokan can detect tsunami at the average of 11.4 minutes earlier than use only the tide gauge currently available at Bitung port. It means that people on the coast of Bitung have more evacuation time before the tsunami hits the coastal area